The Structure of Personality in The Strange Case of Dr. Jekyll and Mr. Hyde by Robert Louis Stevenson: A Study Based on Sigmund Freud's Psychoanalysis - Rio Eka Nugraha; Mc. Fulvia. Hy (Journal of Translation, Linguistics and Literature, 2025)
This study explores the psychological complexity of the main character in Robert Louis Stevenson's The Strange Case of Dr. Jekyll and Mr. Hyde through the lens of Sigmund Freud's psychoanalytic theory, particularly the structure of personality comprising the id, ego, and superego. Set against the backdrop of the morally rigid Victorian era, the novel portrays the internal conflict experienced by Dr. Jekyll, who, driven by the pressures of societal expectations, conducts a dangerous experiment that leads to his transformation into the immoral and impulsive Mr. Hyde. Using a qualitative descriptive method, the research identifies how Dr. Jekyll’s actions embody each aspect of Freud’s personality model: the id is manifested in Hyde’s unrestrained behavior, the ego in Jekyll’s attempts to mediate between his desires and social norms, and the superego in the moral judgment and guilt that eventually lead to his psychological breakdown. The findings reveal that the novel not only illustrates a case of dissociative identity but also offers a profound depiction of the human psyche’s internal struggle for balance between instinct, reason, and morality.